Effect of substrate temperatures on BaCo.1Bi.9O3 NTC thermistor thin films. (15th June 2018) - Li, Sheng; Yuan, Changlai; Liu, Xinyu; Liu, Xiao; Liu, Fei; Luo, Yongwei; Li, Xuqiong; Xu, Jiwen
Abstract: BaCo.1 Bi.9 O3 thin films were successfully prepared by reactive RF magnetron sputtering at different substrate temperature. Crystalline structures, surface morphologies and electrical properties were analyzed by XRD, AFM and resistivity-temperature spectrum. Co ion diffused into the lattice of BaBiO3 to form a solid solution with monoclinic perovskite structure. The root-mean-square value of surface roughness was ~ 4.2 nm for the BCB film deposited at 200 ℃. All thin films exhibited good negative temperature coefficient (NTC) thermistor characteristics. The values of B 25/85, a 25 and ρ 25 of BaCo.1 Bi.9 O3 thin films were in the range of 2538–2730 K, −3.07 to −2.86% K −1 and 345.6–34634.4 Ω cm, respectively. The optimal NTC characteristic ( B 25/85 = 2730 K) with ρ 25 of 345.6 Ω cm was presented in the BaCo.1 Bi.9 O3 thin films grown at 200 ℃ for 4 h. Grains and grain boundaries of BaCo.1 Bi.9 O3 films also showed typical NTC thermistor behavior.